Personalized upper limb orthosis necessitates variety of tools during the development process: hemiplegic child case study - Thomann, Guillaume; de Carvalho, Vinicius A (Disability and rehabilitation: Assistive technology, 2021)
A design methodology for the creation of an upper-limb dynamic orthosis for children was developed in this article. For a non-negligible numerous of cases, orthoses are abandoned for many reasons: they are expensive, heavy, complicated to use, uncomfortable, non-customized, and so on. Three-dimensional (3D) printing technologies are a way to answer a lot of these issues. Moreover, virtual reality and serious games are more and more used in rehabilitation for users' motivation and sometimes for disability evaluation. Microsoft Kinect and Leap Motion technologies combined with games were manipulated to identify the user abilities. Meetings with specialists were made to develop the technical specifications of the orthosis. 3D printer was used with an iterative process for the development of the personalized orthosis. It allowed to progressively focus on the final product thanks to successive prototypes. A Polylactic Acid material was validated with specialists to verify the product reliability. Thirteen prototypes were printed. Technical adjustments were done regarding the 3D printer technology and the molding procedure during the first development cycles. User and physiotherapists were more involved during the 4 final cycles. A combination of design process, technological tools and technical material allowed a 67 g dynamic upper-limb orthosis to be produced, satisfying all technical specifications.Implications for rehabilitationAn iterative design process allows to quickly manufacture and test numerous physical prototypes with design team and final user.Moulding material can be used with 3D printer technologies for facilitating the personalization of the orthosis.Virtual reality and serious game are used as engineering tools to clarify the patient's abilities and needs.